Influence of cutting parameters and tool wear on acoustic emission signal in high-speed turning of Ti-6Al-4V Alloy (2012)
Titanium and its alloys are an important group of engineering materials, with a wide range of applications in aerospace, aircraft, automotive, chemical and biomedical industries. They have excellent combination of strength and fracture toughness as well as low density and excellent corrosion resistance but with poor machinability due to their low thermal conductivity and high chemical reactivity with cutting tool materials. In this study, the effects of cutting parameters and tool wear on the Acoustic Emission (AE) signal in high-speed turning of Ti-6Al-4V alloy with new generation of cemented carbide tools was investigated. Machining trials were conducted at different cutting conditions, the AE signals were acquired and the signal features in the time-domain (mean, standard deviation, amplitude, root mean square, skewness, and kurtosis) and signal features in the frequency-domain (frequency and amplitude) were extracted. The essence of this study was to identifying the features of AE signal capable of being used as potential process indicator for development of automated monitoring and control system for turning of Ti-6Al-4V alloy. The results demonstrated AE signals as potential indicator for Tool Condition Monitoring (TCM) in turning of titanium Ti-6Al-4V alloy.